The ways of improvement of content and pedagogical conditions of preparation of master of preschool education in the context of development of creative potential - Oleksandra Iemchyk (Vasyl Stefanyk Precarpathian National University, 2017)
The necessity of changes in the process of professional preparation of master of preschool education, which is caused by insufficient preparation of graduates to solve problems in this field, low level of creative potential and, as the consequence, unavailability to realization creative pedagogical activity is outlined in the article. The main ways of improvement of content and pedagogical conditions of development of creative potential of master of preschool education in the process of professional preparation are presented: the improvement of content of scientific theoretical preparation of master, studying of progressive pedagogical experience; learning of professional pedagogical disciplines with the reliance to creative tasks with problem search nature; implementation to the educational process of magistracy of institution of higher education on the specialty "Preschool education" of special course "The foundations of development of creative potential of pedagogue"; attraction of students to the creative pedagogical practice; organization and management of students creative process from the side of teachers. There are also identified the perspectives of solution of the problem of development of creative abilities of personality of pedagogue during the professional preparation in the institution of higher education. The implementation of these ways to the educational process will contribute the increasing the readiness of graduates of institutions of higher education to realize pedagogical activity on the creative level, selfdevelopment and self-improvement of their personality. Key words: creative potential of master of preschool education, the professional preparation, the ways of improvement of content of professional preparation.